The Pluscarden Rising. Issue 1 (May 2022) - Watson, Graham
Abstract : This article concludes that the Pluscarden rising is more than the localised protest that previous historians have accepted, and that it was a planned Royalist rising. The story of the rising is outlined before a detailed approach is taken to the people involved. The international context of Royalist planning is examined. A new analysis of the reasons for the rising is then put forward.